Stress Management and its Relationship to Administrative Creativity in the Work Environment of Female Leaders – An experimental Study on the Saudi Women Community - Hareesh, G Jayashree; Alhazmi, Ola (Journal of Posthumanism, 2025)
Work related stress is a common factor that occurs when the work load increase and become beyond the capacity to work. In the modern world, stress at work is a growing and real problem. Stress at work is a major issue for both individuals and organizations. High employee turnover, burnout, absenteeism, illness, low morale, and decreased productivity and performance are all possible outcomes. The majority of workers are unaware that they are under stress. They might act strangely without realizing it, which could affect their performance and health. Additionally, management disregards the fact that a stressful workplace affects not just its workers but also the organization’s productivity. Numerous factors, including organizational and personal ones, can contribute to stress. The study was taken for a sample of 100 working Saudi women. The major findings of the study are married women, women who have completed only their schooling and women aged above 30 years of age undergo high stress at work.